"Like an Expert Sharecropper": Agricultural Halakhah and Agricultural Science in Rabbinic Palestine. Issue 2 (1st December 2014) - Novick, Tzvi
Abstract : The formulation and application of rabbinic Halakhah often depends on the determination of facts that belong, to one degree or another, to the province of professional experts. The resulting structural tension is analogous to that posed by the prominence of the expert witness in the modern American court, or the active role of private industry in administrative law. This article examines the relationship in the classical rabbinic corpus from Palestine between rabbis and farmers, or between rabbinic and agricultural expertise. It considers whether agriculture would have been conceived of in this context as a specialized or technical body of knowledge, and, if so, whether and how agricultural Halakhah accommodates itself to this fact.